2015
DOI: 10.1016/j.foodchem.2015.01.070
|View full text |Cite
|
Sign up to set email alerts
|

Sensory and physicochemical analyses of roasted marama beans [Tylosema esculentum (Burchell) A. Schreiber] with specific focus on compounds that may contribute to bitterness

Abstract: The role of phenolics and saponins in contributing to bitterness in marama beans, an underutilized legume, especially when roasted, was investigated. Marama beans were roasted at 150 °C for 20, 25 or 30 min, dehulled to separate cotyledons, and pastes were prepared from these. Water extracts were prepared from full fat and defatted flours from roasted and unroasted marama cotyledons. A sensory panel evaluated the sensory attributes of marama pastes and water extracts. Marama water extracts were analysed for to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…According to the literature, the roasting process affects the phenolics of nuts such as cashew nut, hazelnut and peanut, leading to alteration of their antioxidant activities [112,113]. Nyembwe et al [114] reported that the contents of gallic acid and protocatechuic acid were increased from 34.8 and 78.0 to 81.0 and 123.0 mg/100 g DW of flour, respectively, upon roasting at 150 °C for 30 min, possibly due to the release of bound phenolics during the process. Chandrasekara and Shahidi [115] reported that the protection factor by the Rancimat assay and total phenolic content of phenolic extracts from the cashew nuts was increased by both the low and high temperature roasting treatment and discussed that the improvement can be induced by liberation of bound phenolics during the roasting process.…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature, the roasting process affects the phenolics of nuts such as cashew nut, hazelnut and peanut, leading to alteration of their antioxidant activities [112,113]. Nyembwe et al [114] reported that the contents of gallic acid and protocatechuic acid were increased from 34.8 and 78.0 to 81.0 and 123.0 mg/100 g DW of flour, respectively, upon roasting at 150 °C for 30 min, possibly due to the release of bound phenolics during the process. Chandrasekara and Shahidi [115] reported that the protection factor by the Rancimat assay and total phenolic content of phenolic extracts from the cashew nuts was increased by both the low and high temperature roasting treatment and discussed that the improvement can be induced by liberation of bound phenolics during the roasting process.…”
Section: Resultsmentioning
confidence: 99%
“…Marama beans were collected from the Masokaphala area, Botswana (Nyembwe, Minnaar, Duodu, de Kock, 2015). Wheat flour (Snowflake, Premier, South Africa), cassava starch (CS) (Nature's Choice, Atlantis, South Africa), instant yeast and salt were obtained from retail stores.…”
Section: Methodsmentioning
confidence: 99%
“…It well known that process of roasting may lead to significant changes in the chemical composition of legume seeds (Nyembwe et al, 2015). With several exceptions (e.g.…”
Section: Resultsmentioning
confidence: 99%